PEMETAAN POTENSI KEMAMPUAN LAHAN UNTUK PENGEMBANGAN KOPI DI KECAMATAN SAMBAS BERDASARKAN SIFAT FISIK TANAH BERBASIS SISTEM INFORMASI GEOGRAFIS - Sudirman Masara’T; Sunardi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The plantation sector is one of the area utilization activities that is able to contribute significantly to the income of rural communities, both in providing employment and earning potential foreign exchange. These conditions are not supported by digitally integrated regional development information. This study aims to map the potential development of coffee plants in Sambas sub-district based on the physical properties of land presented in the form of digital maps. The research was conducted in six villages within the administrative area of Sambas sub-district using purpose sampling method. In each village, 3 locations will be selected as soil sampling plots with the area of each plot is 1 ha and each soil sample plot is taken diagonally. The distance between each sampling plot is 5 km. Soil samples from each plot are then analyzed in the soil laboratory. The results of the analysis are then processed using quantum GIS software to obtain a digital-based map of land development potential.